Inside Cover: Ordered Macro/Microporous Ionic Organic Framework for Efficient Separation of Toxic Pollutants from Water (Angew. Chem. Int. Ed. 1/2023). Issue 1 (14th December 2022) - Fajal, Sahel; Hassan, Atikur; Mandal, Writakshi; Shirolkar, Mandar M.; Let, Sumanta; Das, Neeladri; Ghosh, Sujit K.
Abstract : Energy‐economic separation of a wide array of toxic pollutants from water using macro–micro hierarchical pores crafted in an ionic organic framework is reported by Sujit K. Ghosh et al. in their Research Article (e202214095) . The uniformly distributed ordered interconnected macropores in synergy with charged viologen units demonstrated swift diffusion of analytes, thus achieving ultrafast adsorption potency toward various organic–inorganic toxic contaminants from water.